Analisis Penerapan Isak 35 Tentang Penyajian Laporan Keuangan Pada Organisasi Nonlaba (Studi Kasus Pada Yayasan Pembina Universitas Islam Nusantara) - Astriani, Maudi; Heriyanto (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
The foundation, as a non-profit organization in presenting financial statements refers to Interpretation of Financial Accounting Standards 35 or ISAK 35. However, many non-profit organizations have difficulty implementing it due to a lack of accounting understanding. This study aims to determine the application of ISAK 35 and the impact of the application of ISAK 35 on financial transparency and accountability at Yayasan Pembina Universitas Islam Nusantara. Data were collected through observation, interviews, and documentation with a qualitative descriptive method. The results show that the Foundation which is the object of research has applied ISAK 35 to the presentation of financial statements and the application of ISAK 35 increases the transparency and accountability of the foundation's financial statements, although there are still improvements needed in recording income and allocation of funds.